Individual social capital as an asset of personal marketing in the job search process. - Matias Membiela-Pollań; Va Martinez-Fernandez; Oścar Juanatey-Boga (The Central European Review of Economics and Management (CEREM), 2019)
Aim: The aim of this study is to highlight the role of individual social capital as a personal marketing asset with specific weight in the job search process. The marketing mix instruments are transferred to the analysis of the individual. In this approach, the social network and the attributes of the subject play a specific role in his characteristics as a "product", in his "promotion" and "distribution", and in his "price", which in this case is the salary.~Design/Research methods: The methodology used to elaborate this work is based on an exploratory analysis, and seeks to establish a state of the art from the literature on "individual social capital" and "personal marketing". For this, firstly, both concepts are considered, and secondly, the individual social capital as an asset of personal marketing in the job search process is studied, using the tools of the marketing mix (4 P's).~Conclusions/findings: Based on the analysis carried out, we conclude that individual social capital is decisive in the development of personal marketing, whose ultimate goal is to find a job and get a higher income.~Originality/value of the article: The originality of this article lies in applying the tools of the marketing mix to the individual, and considering it as a "product" that wants to be demanded in the labor market; highlighting also the role that individual social capital plays in this process.
Keywords: A12; M31; 330; Personal marketing; individual social capital; social network; promotion; employment; income